Structures of Time in the Mentality of the English Burghers During 11th–13th Centuries - Охріменко О. (Видавничо-поліграфічний центр "Київський університет", 2013)
The article based on narrative and visual sources and it investigates the perception of time as a social category of urban residents in England during the eleventh to thirteenth centuries. It identifies the changes that occur in the mentality of the English society under the influence of urbanization processes of the High Middle Ages.

У статті на основі наративних та зображальних джерел досліджується сприйняття часу як соціальної категорії міськими жителями Англії у період ХІ–ХІІІ ст. Визначаються зміни, що відбуваються у ментальності англійського суспільства, під впливом урбанізаційних процесів доби високого середньовіччя.
Часові структури у ментальності англійського бюргерства ХІ–ХІІІ ст.
Keywords: social history; the history of time; the medieval mentality; England; urbanization; соціальна історія; історія часу; середньовічна ментальність; Англія; урбанізація